PENGARUH GAYA KEPEMIMPINAN SITUASIONAL KEPALA DESA TERHADAP KINERJA PEGAWAI - Sepia Diana Putri; Yuliasih Yuliasih; Septina Suci Dewi; Anang Sugeng Cahyono (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The success of village development is highly dependent on the role of the village head and his staff. Situational leadership style is one alternative that influences employee performance. This study examines more deeply various phenomena such as low education levels, lack of work discipline, lack of training/workshops for employees.  The method used is descriptive and literature study. The purpose of this study was to determine the extent of the influence of the situational leadership of the village head on employee performance. In situational leadership according to Hersey & Blanchard (2006), there are four types of leadership, namely telling (directing), selling (training), participation (mobilizing participation), delegating (delegating). There are also performance indicators according to Sedamaryanti (2014: 198), namely clear specifications, objectively measurable, relevant, achievable, flexible, effective. If the type of leadership and performance indicators are linked, it can be concluded that the situational leadership of the Gondanggunung Village Head has not significantly influenced employee performance